2010
DOI: 10.1103/physrevlett.104.106102
|View full text |Cite
|
Sign up to set email alerts
|

Wetting of Nanopatterned Grooved Surfaces

Abstract: The wetting by perfluoromethylcyclohexane of a well-defined silicon grating with a channel width of 16 nm has been studied using transmission small angle x-ray scattering. Prefilling, capillary filling, and postfilling wetting regimes have been identified. A detailed comparison of the data with theory reveals the importance of long-ranged substrate-fluid and fluid-fluid interactions for determining the wetting behavior on these length scales, especially at the onset of capillary condensation and in the prefill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 18 publications
3
57
0
1
Order By: Relevance
“…The atomic structure of the liquid metal and of the substrate becomes important on the nano-scale, and nano-wetting properties have an important influence on the macroscopic wetting behavior of liquids on solid surfaces. 4,6,8 The wetting properties of the liquid metal/ceramic interface are strongly affected by the composition of the solid and liquid components, the roughness and other irregularities on the macro level, or grain-boundary grooves and lattice pits at the micro-scale, the surface pattern of the ceramic substrate, and either the reactive or non-reactive wetting, by the mechanisms occurring at the nano scale, including thermal influences. [4][5][6][7][15][16][17] Although the geometrically structured substrates were a matter of interest for years 18 at macro and micro scale, they can be investigated in a new light, since the recent development of experimental techniques at the nano level, as well as of accompanied theories.…”
Section: A Nano-scale Mechanism -The Fractional Surface Approcahmentioning
confidence: 99%
See 3 more Smart Citations
“…The atomic structure of the liquid metal and of the substrate becomes important on the nano-scale, and nano-wetting properties have an important influence on the macroscopic wetting behavior of liquids on solid surfaces. 4,6,8 The wetting properties of the liquid metal/ceramic interface are strongly affected by the composition of the solid and liquid components, the roughness and other irregularities on the macro level, or grain-boundary grooves and lattice pits at the micro-scale, the surface pattern of the ceramic substrate, and either the reactive or non-reactive wetting, by the mechanisms occurring at the nano scale, including thermal influences. [4][5][6][7][15][16][17] Although the geometrically structured substrates were a matter of interest for years 18 at macro and micro scale, they can be investigated in a new light, since the recent development of experimental techniques at the nano level, as well as of accompanied theories.…”
Section: A Nano-scale Mechanism -The Fractional Surface Approcahmentioning
confidence: 99%
“…4,6,8 The wetting properties of the liquid metal/ceramic interface are strongly affected by the composition of the solid and liquid components, the roughness and other irregularities on the macro level, or grain-boundary grooves and lattice pits at the micro-scale, the surface pattern of the ceramic substrate, and either the reactive or non-reactive wetting, by the mechanisms occurring at the nano scale, including thermal influences. [4][5][6][7][15][16][17] Although the geometrically structured substrates were a matter of interest for years 18 at macro and micro scale, they can be investigated in a new light, since the recent development of experimental techniques at the nano level, as well as of accompanied theories. 4,6,19 It is shown that a change in the type of liquid metal/ substrate interface, in the same system (Ni-Si/C system with a formed reaction layer of SiC and hence an interface change), leads to a remarkable change in the wetting: from contact angles much higher than 90°to contact angles in the range 20-40°.…”
Section: A Nano-scale Mechanism -The Fractional Surface Approcahmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, the structure and properties of the confining surfaces may be exploited to efficiently manipulate the behaviour of fluids which are in contact with them. Recent progress in controlled fabrication of patterned solid surfaces at the nano-to micro-meter range [1][2][3][4][5][6] open excellent prospects in tailoring interfacial forces which in turn can be used to control the behaviour of adsorbed fluids. Apart from an academic interest, a fundamental understanding of such systems will pave the way for the design and manufacturing of novel materials, devices, and applications.…”
Section: Introductionmentioning
confidence: 99%